PENGARUH E-SERVICE QUALITY DAN TRUST TERHADAP KEPUTUSAN PEMBELIAN ONLINE SHOP SHOPEE PADA KARYAWAN PLANT F PT. CHANGSIN INDONESIA - Suwaebah Islamiyah; Ratnasari, Ina (Journal for Management Student (JFMS), 2021)
This study aims to determine, analyze, and explain the trust and e-service quality of employees of plant F PT. Changsin Indonesia on Shopee's online shop. The method used in this research is a quantitative approach with descriptive verification. The sample used is 213 employees of PT. Schangsin Indonesia, with problem solving techniques using path analysis through the stages of testing data validity and data transformation. The results showed that trust, e-service quality and purchasing decisions for employees of plant F PT. Changsin Indonesia in the Shopee Online shop is in the good category. The trust variable with e-service quality has a low level of relationship. Partially trust and e-service quality have a significant positive effect on purchasing decisions at Shopee's online shop. And overall that trust and e-service quality have a significant positive effect on purchasing decisions, because trust and e-service quality are part of making consumer purchasing decisions at Shopee's online shop. Keywords: trust, e-service quality and purchasing decisions